A Philosophical Review of Justice in Legal Aid after Indonesia's Budget Efficiency Policy - Libra, Robert; Muhammad Fauzan (Universitas Islam Negeri Raden Intan Lampung, 2025)
The concept of legal aid in Indonesia has evolved from a voluntary practice of generosity to a constitutional right, reflecting the principles of equality before the law and distributive justice. This transformation aligns with Articles 27 and 28D of the 1945 Constitution of the Republic of Indonesia and Law No. 16 of 2011, obligating the state to remove economic barriers that hinder the poor's access to justice. Legal aid funding through the State Budget affirms the state's moral and legal responsibility to protect human rights, particularly the right to receive legal aid. However, Presidential Instruction No. 1 of 2025, which focuses on expenditure efficiency, threatens to reduce this funding. This study aims to analyze the concept of legal aid from the perspective of justice philosophy and examine the dilemma between efficiency and justice in Indonesia's legal aid system. Employing a normative juridical approach with statutory and conceptual analysis. The research findings indicate that legal aid embodies John Rawls' Difference Principle, advocating a bias toward the disadvantaged. The Presidential Instruction on Efficiency presents a normative dilemma, balancing administrative efficiency with constitutional duties. Excluding legal aid funding under this policy risks undermining fundamental legal values, potentially widening inequality, and violating human dignity. The philosophical evolution of legal aid as a constitutionally guaranteed right faces an ethical dilemma when efficiency measures conflict with the state's responsibility to uphold justice, disproportionately harming vulnerable groups and threatening the welfare state's commitment to equality before the law.